The Anti-apoptosis Effect of Single Electroacupuncture Treatment via Suppressing Neuronal Autophagy in the Acute Stage of Ischemic Stroke Without Infarct Alleviation - Xing, Ying; Zhang, Min; Wang, Man-Man; Feng, Ya-Shuo; Dong, Fang; Zhang, Feng (Frontiers in Cellular Neuroscience, 2021)
The main purpose of the study was to investigate the antiapoptotic effect of electroacupuncture (EA) in the acute stage of ischaemic stroke in rats. The cerebral ischemia model was established by middle cerebral artery occlusion (MCAO)/reperfusion in rats. A single EA treatment was performed at the acute stage of ischaemic stroke. The neurological function, brain water content, apoptotic cell number, and cerebral infarct volume were assessed in stroke rats. The expression of autophagy-related proteins (LC3II/I, Beclin1, P62, and LAMP1), Sirtuin 1 (SIRT1), p-JNK, p-ERK1/2, and cleaved caspase-3 (CCAS3) were measured by Western blot, immunofluorescence, and immunohistochemistry. Rapamycin (RAP, an activator of autophagy) was used to confirm the antiapoptotic effect of EA via regulating autophagy. The brain edema infarct size and apoptotic cell number were increasing within 3 days following stroke, and brain edema reached its peak at 24 h after stroke. EA treatment at 24 h after ischaemic stroke obviously suppressed the number of apoptotic cells and brain edema. However, there were no significant differences in infarct volumes among EA-12 h, EA-24 h, and MCAO/R group. Moreover, EA treatment at 24 h after ischaemic stroke obviously suppressed the expression of CCAS3, LC3II/I, Beclin1 while increasing the level of P62 and LAMP1 and hence mediating autophagy, which was reversed by RAP. Meanwhile, the expression of SIRT1, p-ERK1/2, p-JNK were promoted by EA at 24 h after ischaemic stroke. In conclusion, EA treatment may suppress apoptosis possibly via regulating autophagy in the acute period after ischaemic stroke, hence reducing brain injury.